Common Clinical Presentations of GBV Survivors Seen Between 2020-2022 at a GBV Clinic in a Tertiary Care Referral Facility in South East Nigeria - H.C Uro-Chukwu; U.O Anyanwu, (Journal of Women's Reproductive Health, 2022)
Background Gender based violence (GBV) refers to any violence targeted at an individual or group on the basis of their gender. It could occur in different forms with several clinical manifestations. The authors have described several clinical manifestations of GBV in a tertiary health centre, knowledge of which would help in case identification and early clinical management. Methods Retrospective descriptive study of all clients seen at a gbv clinic over a sixteen months period.Data was obtained from case records and clinical presentations were entered into excel. Data analysis was done usingIBM SPSS Statistics for Windows, version 25. The results were presented in frequency tables and graphs Results Of 86 clients studied, 56(65.1%) were of pediatric age (< 18years) while 30(34.9%) were adults with a mean age of 18.33+11.64(range 1-64years).72(82.6%) belonged to the low social class. Physical abuse in the forms of battering, human bite, walking and sitting disturbances, hearing loss possibly from slapping or hitting and red eye possibly from trauma on the eye, constituted 37.6% of the clinical presentations. Other presentations were; sexual abuse in the form of forced sex which constituted 34.9%, while gynaecological / obstetrics presentations in the forms of bleeding per vagina, pregnancy due to forced sex and vaginal pain made up 13.9%. Emotional/psychological abuse was observed in all clients irrespective of their different presenting complaints. Conclusion While various forms of physical abuse were common, emotional abuse was present in all clients but masked probably due to prioritization of physical injuries. Therefore we recommend that all GBV survivors be screened for psycholocal abuse and psychotherapy given.
Keywords: GBV